Full donor chimerism after allogeneic hematopoietic stem cells transplant for myelofibrosis: The role of the conditioning regimen. Issue 2 (30th November 2020) - Chiusolo, Patrizia; Bregante, Stefania; Giammarco, Sabrina; Lamparelli, Teresa; Casarino, Lucia; Dominietto, Alida; Raiola, Anna Maria; Metafuni, Elisabetta; Di Grazia, Carmen; Gualandi, Francesca; Sora, Federica; Laurenti, Luca; et al.
Abstract: The aim of this retrospective study was to assess the rate of full donor chimerism (F‐DC) in patients with myelofibrosis, prepared for an allogeneic stem cell transplant, with one or two alkylating agents. We analyzed 120 patients with myelofibrosis, for whom chimerism data were available on day +30. There were two groups: 42 patients were conditioned with one alkylating agent (ONE‐ALK), either thiotepa or busulfan or melphalan, in combination with fludarabine, whereas 78 patients were prepared with two alkylating agents, thiotepa busulfan and fludarabine (TBF). Patients receiving TBF were older (57 vs 52 years), were less frequently splenectomized pre‐HSCT (31% vs 59%), had more frequently intermediate‐2/high DIPSS scores (90% vs 74%), were grafted more frequently from alternative donors (83% vs 33%) and received more frequently ruxolitinib pre‐HSCT (26% vs 7%). The proportion of patients with F‐DC on day +30, in the TBF vs the ONE‐ALK group, was respectively 87% vs 45% ( P < .001). The 5‐year cumulative incidence of relapse was 9% in the TBF group, vs 43% for the ONE‐ALK group ( P < .001). The 5‐year actuarial disease‐free survival was 63% for TBF and 38% for the ONE‐ALK group ( P = .004). In conclusion, early full donor chimerism is a prerequisite for long term control of disease in patients with myelofibrosis, undergoing an allogeneic HSCT. The combination of two alkylating agents in the conditioning regimen, provides a higher chance of achieving full donor chimerism on day+30, and thus a higher chance of long term disease free survival.